Coupling generalized FC model to meshless EFG method for crack growth analysis in quasi-brittle materials - Cichoń, Czesław; Jaśkowiec, Jan (Computer Assisted Methods in Engineering and Science, 2023)
In the paper a crack growth analysis in quasi brittle materials in plane stress state coupling the Fictitious Crack model to meshless Element-Free Galerkin method is presented. The FC model has been generalized and as a result a uniform algorithm of the analysis of crack propagation, which is a combination of elementary states mode I and mode II has been prepared. The problem is nonlinear because the traction forces contain, besides external loads, cohesive forces on the boundaries of the crack which depend on the actual state of the displacement field. The efficiency of the method has been tested on two standard examples.